Effects on rumen microbiome and milk quality of dairy cows fed a grass silage-based diet supplemented with the macroalga Asparagopsis taxiformis - Krizsan, Sophie J.; Ramin, Mohammad; Chagas, Juana C. C.; Halmemies-Beauchet-Filleau, Anni; Singh, Abhijet; Schnürer, Anna; Danielsson, Rebecca (Frontiers in Animal Science, 2023)
The objective was to determine the effects on rumen microbiome and milk quality of reducing the methane (CH4) produced from enteric fermentation by the addition of Asparagopsis taxiformis (AT) to the diets of dairy cows. Six Nordic Red cows at 122 ± 13.7 (mean ± SD) days in milk, of parity 2.7 ± 0.52 and producing 36 kg ± 2.5 kg milk per day at the start of the trial were divided into three blocks by milk yield and assigned to an extra-period Latin-square change-over design comprising two dietary treatments. An extra period of observation was added to the Latin-square change-over design to control for carry-over effects. The dietary treatments were a diet consisting of grass silage and a commercial concentrate mixture (60:40) either not supplemented or supplemented with 0.5% AT on an organic matter intake basis. On average, daily CH4 production, CH4 yield, and CH4 intensity decreased by 60%, 54%, and 58%, respectively, in cows fed the diet supplemented with AT. Furthermore, hydrogen gas emitted by cows fed diets supplemented with AT increased by more than five times compared with cows fed a non-AT-supplemented diet. Feed intake was decreased and milk production altered, reflecting a decreased yield of milk fat in cows fed an AT-supplemented diet, but feed efficiency increased. Rumen fermentation parameters were changed to promote propionate rather than acetate and butyrate fermentation. The most prominent change in milk quality was an increase in bromine and iodine when the diet was supplemented with AT. The reduction in CH4 was associated with a shift from Methanobrevibacter to Methanomethylophilaceae in the archaeal population and a lower relative abundance of Prevotella in the bacterial population. Changes in milk fat odd-numbered and branched-chain fatty acids in the current study of AT supplementation support observed differences in ruminal archaeal and bacterial populations.